Supporting Children's Resettlement ('Reentry') After Custody: Beyond the Risk Paradigm. (April 2021) - Hazel, Neal; Bateman, Tim
In response to policy concerns in England and Wales and internationally, a considerable knowledge base has identified factors statistically associated with reduced recidivism for children leaving custodial institutions. However, despite resulting guidance on how to support resettlement ('reentry'), practice and outcomes remain disappointing. We argue that this failure reflects weaknesses in the dominant 'risk paradigm', which lacks a theory of change and undermines children's agency. We conceptualise resettlement as a pro-social identity shift. A new practice model reinterprets existing risk-based messages accordingly, and crucially adds principles to guide a child's desistance journey. However, successful implementation may require the model to inform culture change more broadly across youth justice.